Roundabout 4 Regulates Blood–Tumor Barrier Permeability Through the Modulation of ZO-1, Occludin, and Claudin-5 Expression. Issue 1 (January 2015) - Cai, Heng; Liu, Wenjing; Xue, Yixue; Shang, Xiuli; Liu, Jing; Li, Zhen; Wang, Ping; Liu, Libo; Hu, Yi; Liu, Yunhui
<x xml:space="preserve">Abstract</x> Abstract The blood–tumor barrier (BTB) restricts the delivery of chemotherapeutic drug molecules to tumor tissues. We found that the endothelial cell (EC) receptor molecule Roundabout 4 (Robo4) is endogenously expressed in human brain microvascular ECs and that it is upregulated in a BTB model of glioma cocultured ECs. Knockdown of Robo4 in this BTB model increased permeability; short hairpin RNA targeting Robo4 (shRobo4) led to decreased transendothelial electric resistance values, increased BTB permeability, and downregulated expression of the EC tight junction proteins ZO-1, occludin, and claudin-5. Roundabout 4 influenced BTB permeability via binding with its ligand, Slit2. Short hairpin RNA targeting Robo4 also increased matrix metalloproteinase-9 (MMP-9) activity and expression in glioma cocultured ECs; pretreatment with the MMP inhibitor GM6001 partially blocked the effects of shRobo4 on the transendothelial electric resistance values and ZO-1 and occludin expression. Short hairpin RNA targeting Robo4 also upregulated the phosphorylation of Src and Erk1/2; the Src inhibitor PP2 and the Erk1/2 inhibitor PD98059 blocked shRobo4-mediated alteration in ZO-1 and occludin expression. Together, our results indicate that knockdown of Robo4 increased BTB permeability by reducing EC tight junction protein expression, and that the Src–Erk1/2–MMP-9 signal pathways are involved in this process. Thus, Robo4 may represent a useful future therapeutic target for enhancing BTB permeability.